1996
DOI: 10.1007/bf01877246
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of potato virus YN isolates by PCR-RFLP

Abstract: Based on the sequence polymorphism in the 5' terminal part of the viral genome, a range of PVY N isolates were characterized by polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP). Three pairs of primers selected in the 5' non-translated and P1 protein region were tested. Two of them yielded PCR products of about 1Kb from all isolates tested. Restriction analysis of the PCR products gave two distinct electrophoretic patterns, whichever of the three enzymes was used. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 28 publications
(32 reference statements)
3
22
0
Order By: Relevance
“…To corroborate our results, we compared the findings of the Nco I/Bgl II method with those of the RFLP analysis of Glais et al (1996). Of the three enzymes that were used by those authors we found Hinc II to be the most reliable: although it cleaved the PCR products of both N and NTN strains, the numbers of cleavage sites differed between the strains: one in the NTN and two in the N (see Figs 1 and 4).…”
Section: Test For Pvy Nlw In Field Samplessupporting
confidence: 81%
See 3 more Smart Citations
“…To corroborate our results, we compared the findings of the Nco I/Bgl II method with those of the RFLP analysis of Glais et al (1996). Of the three enzymes that were used by those authors we found Hinc II to be the most reliable: although it cleaved the PCR products of both N and NTN strains, the numbers of cleavage sites differed between the strains: one in the NTN and two in the N (see Figs 1 and 4).…”
Section: Test For Pvy Nlw In Field Samplessupporting
confidence: 81%
“…Some of the enzymes which were previously used (Glais et al, 1996) differentiated between the N and NTN strains but they cleave at several sites within the virus amplicons of both the NTN and N strains (e.g., Taq I and Hinc II). Others (Ava II) cleave similarly in the amplicons of both strains (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptomology results described above showed that typical pepper-PVY isolates were distinguished from potato isolates by host range (8). After phylogenetic analysis we noticed that pepper isolate has high similarity with LYE84.2 strain that was isolated from tomato (6) and with SON41 strain witch was isolated from C. annuum (5). For this reason pepper infecting isolates could be classified within the PVY NP group that expanding earlier suggestions made by Romero et al (10).…”
Section: Discussionsupporting
confidence: 67%